Policy to practice: an implementation case study in restorative justice - Sliva, Shannon (Contemporary justice review, 2020)
This case study of a Colorado county with high statutory support for restorative justice uses interviews with Primary Implementers and secondary data to identify the key determinants of policy implementation in state agencies. Results suggest that state-level restorative justice policies have been implemented to varying degrees by local agencies. Uptake is most associated with the actions of championing agency administrators and the availability of designated funding. Incomplete implementation can be at least partially attributed to organizational value conflicts, role confusion, insufficient funding, and capacity limitations. Findings in this case suggest that successful implementation of restorative justice policy requires a high level of subsequent commitment from the state, implementing agencies, and the community. Current policy debates about restorative justice and other alternative approaches to justice may be meaningless if policy structure, funding support, and state organizational capacity are not accounted for. Even the most supportive policy context must be supplemented by organizational infrastructure and buy-in.